2017
DOI: 10.1523/eneuro.0262-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Neuroprosthesis Merges Visible and Invisible Light Without Impairing Native Sensory Function

Abstract: Adult rats equipped with a sensory prosthesis, which transduced infrared (IR) signals into electrical signals delivered to somatosensory cortex (S1), took approximately 4 d to learn a four-choice IR discrimination task. Here, we show that when such IR signals are projected to the primary visual cortex (V1), rats that are pretrained in a visual-discrimination task typically learn the same IR discrimination task on their first day of training. However, without prior training on a visual discrimination task, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…This means experiences to which the brain has never been exposed to, neither during critical periods of the specific user nor during the entire history of human evolution. In animals models, NSEs were successfully elicited invasively (Hartmann et al, 2016;Thomson et al, 2017Thomson et al, , 2013.In humans, however, we must find a way to convey NSEs noninvasively via our existing sensory channels, thus making SSDs perfect tools for this approach. Examples of such experiences can be infrared (IR) vision conveyed through sound or ultrasound perception through touch.…”
Section: Does the Concept Of Reversible Plasticity Gradient Extend Almentioning
confidence: 99%
“…This means experiences to which the brain has never been exposed to, neither during critical periods of the specific user nor during the entire history of human evolution. In animals models, NSEs were successfully elicited invasively (Hartmann et al, 2016;Thomson et al, 2017Thomson et al, , 2013.In humans, however, we must find a way to convey NSEs noninvasively via our existing sensory channels, thus making SSDs perfect tools for this approach. Examples of such experiences can be infrared (IR) vision conveyed through sound or ultrasound perception through touch.…”
Section: Does the Concept Of Reversible Plasticity Gradient Extend Almentioning
confidence: 99%
“…Prior work has shown that rats can learn to discriminate between 4 potential goal locations on the basis of ICMS delivered when their heading coincides with the direction of the true goal location (35). Several variations on this result were subsequently reported (26,36,37). Our sensory BMI experiment also used a searching task with goal direction feedback.…”
Section: Discussionmentioning
confidence: 76%